How user-generated content on social media platform can shape consumers’ purchase behavior? An empirical study from the theory of consumption values perspective - Du Thi Chung (Cogent Business & Management)
This study investigates the impact user-generated content (UGC) on consumer purchase behavior, employing the framework of consumption value theory. A conceptual model was proposed and tested to evaluate the effects of perceived value from UGC, attitude toward UGC, and UGC adoption on consumer purchase behavior. Data were collected from 445 social media users via web-based and paper-based surveys in three big cities in Vietnam, an emerging market within the Asian region. Based on this theoretical background, this study suggests that the overall perceived value of user-generated content is conceptualized as a second-order multidimensional formative construct, consisting of functional, social, and emotional value as reflective first-order dimensions. Using partial least squares structural equation modeling (PLS-SEM), the results indicate that functional, social, and emotional values significantly contribute to the overall UGC value. Perceived overall value from UGC positively influences attitudes toward UGC and UGC adoption. Furthermore, UGC adoption is positively affected by perceived value and attitudes toward UGC. Notably, although there is no direct impact on purchase behavior, the overall value of UGC indirectly influences purchase behavior through both attitudes toward UGC and UGC adoption. The theoretical and practical implications of these findings are then discussed and proposed.